2012
DOI: 10.1089/neu.2011.2247
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Cranial Defects with Individually Formed Cranial Prostheses Made of Polypropylene Polyester Knitwear: An Analysis of 48 Consecutive Patients

Abstract: This article presents a new method of cranioplasty in which polypropylene polyester knitwear was used as the filling material. The basis for prosthesis shaping was a three-dimensional model of the defect made according to the patient's CT scans. Previously, such material has never been a subject of computer-aided design and computer-aided manufacturing (CAD/CAM) individual forming. The process of the prosthesis design included CT bone scans and mold preparation for each patient. Such prostheses were implanted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…There were no cases of infection reported in previously published series [ 13 , 28 ], but a proportion of craniotomies for tumours will unfortunately develop infection requiring craniotomy flap explantation, whether this was a primary untreated bone (2% [ 21 ]), autoclaved bone (up to 4% [ 24 ]), bone autologous graft (up to 5% [ 9 ]), or an allograft (Table 2 , up to 17% [ 17 ]). Table 2 summarises studies of cranioplasty for bone-invasive meningioma [ 3 , 6 , 12 , 15 , 17 , 19 , 22 ]. One of our cases underwent removal of the titanium mesh in the absence of infection (Case 3).…”
Section: Discussionmentioning
confidence: 99%
“…There were no cases of infection reported in previously published series [ 13 , 28 ], but a proportion of craniotomies for tumours will unfortunately develop infection requiring craniotomy flap explantation, whether this was a primary untreated bone (2% [ 21 ]), autoclaved bone (up to 4% [ 24 ]), bone autologous graft (up to 5% [ 9 ]), or an allograft (Table 2 , up to 17% [ 17 ]). Table 2 summarises studies of cranioplasty for bone-invasive meningioma [ 3 , 6 , 12 , 15 , 17 , 19 , 22 ]. One of our cases underwent removal of the titanium mesh in the absence of infection (Case 3).…”
Section: Discussionmentioning
confidence: 99%
“…is result was predictable given the technical difficulties of adequately reproducing the normal shape and cranial conformation; the data were widely discussed in the literature, in which many authors showed the superiority of the cosmetic result of custom-made prostheses, both in titanium [3,13,21] and in other biomaterials such as HA, PMMA, and PEEK. [8,9,[14][15][16]25] An adequate aesthetic result is of great importance both for the psychological perspective of the patient and their relatives and because, in some cases, a prostheses with inadequate curvature can promote pain in the temporal region or skin decubitus which, in turn, can cause the prostheses to fail. It is for these reasons that the cosmetic result is considered one of the main outcomes of cranioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Several other polymers have been investigated for large format cranial implants: PEEK (poly-ether-ether ketone), 36 Polypropylene Polyester Knitwear, 37 and PEKK (Poly-ether-ketone ketone) (Figure 4). 38 There is also an FDA-approved PEKK custom cranial implant product (Oxford Performance Materials, South Windsor, CT).…”
Section: Advances In Alloplastic Bone Substitutes For Cranial Repairmentioning
confidence: 99%